Pengaruh Fisioterapi Baby spa terhadap Peningkatan Berat Badan Bayi Usia 3-9 Bulan - Elok Ghina Fadhilah; Nurul Halimah; Puspo Wardoyo; Angria Pradita (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Babies who are underweight are more at risk for malnutrition, hypoglycemia and impaired growth and development that must be treated immediately. Some physiotherapy treatments to increase baby's weight include consultation on growth and development, nutrition, breastfeeding assistance, complementary foods and relaxation treatments. Baby spa is a relaxation method that can give babies weight gain. This research method is a quantitative experimental pre test & post test control group design using 24 samples of male and female infants, with an age range of 3 - 9 months which were taken randomly and divided into 2 treatment groups. The treatments in group 1 are; Infant care is carried out in the form of consultation on growth and development, nutrition, breastfeeding and complementary feeding assistance. Treatment in group 2, namely; baby care was carried out in the form of consultation on growth and development, nutrition, breastfeeding assistance, complementary foods and giving Baby spa treatment. Both groups were measured body weight before and after 4 interventions, every 2 weeks which lasted for 2 months. In the measurement of infant weight before and after the intervention, the median value of Group 1; 68.7 (50.2-71.0) to 71.5 (57.1–76.1), Group 2; 61.7 (51.0–72.6) to 15.1 (69.0–86.5) with a P value of 0.002 < 0.05. It can be concluded in this study that the provision of Baby spa Physiotherapy has a significant effect on increasing the weight of babies aged 3-9 months.Keywords: baby spa; baby's weight; relaxationABSTRAKBayi yang berat badannya kurang, lebih berisiko mengalami gizi kurang, hipoglikemia dan gangguan tumbuh kembang yang harus segera ditangani. Beberapa tata laksana fisioterapi untuk meningkatkan berat badan bayi meliputi konsultasi tumbuh kembang, gizi, pendampingan ASIP, MPASI dan treatment relaksasi. Baby spa adalah salah satu metode relaksasi yang mampu memberi peningkatan berat badan pada bayi. Metode penelitan ini adalah kuantitatif eksperimental pre test & post test control group design menggunakan 24 sampel penelitian bayi lakilaki dan perempuan, dengan rentang usia 3 – 9 bulan yang diambil secara acak dan dibagi 2 kelompok perlakuan. Perlakuan pada kelompok 1 yakni; dilakukan perawatan bayi berupa konsultasi tumbuh kembang, gizi, pendampingan ASIP dan MPASI. Perlakuan pada kelompok 2 yakni; dilakukan perawatan bayi berupa konsultasi tumbuh kembang, gizi, pendampingan ASIP, MPASI dan pemberian treatment Baby spa. Kedua kelompok dilakukan pengukuran berat badan sebelum dan sesudah 4 kali intervensi, setiap 2 minggu sekali yang berlangsung selama 2 bulan. Pada pengukuran berat badan bayi sebelum dan sesudah intervensi, nilai median Kelompok 1; 68,7 (50,2-71,0) menjadi 71,5 (57,1–76,1), Kelompok 2; 61,7 (51,0–72,6) menjadi 15,1 (69,0–86,5) dengan pvalue 0,002 < 0,05. Bisa disimpulkan bahwa pemberian fisioterapi baby spa secara signifikan berpengaruh dalam peningkatan berat badan bayi usia 3-9 bulan.Kata kunci: baby spa; berat badan bayi; relaksasi